Anti-bacterial compounds from Indian curry-leaf tree Murraya koenigii have potential to inhibit carbapenem-resistant Streptococcus pneumoniae - Soumya Basu; Balaji Veeraraghavan; Anand Anbarasu (Elsevier, 2024)
Problems considered: Spike in the mortality rates due to pneumococcal infections post-COVID-19 has raised clinical concerns globally. β-lactam antibiotic-susceptibility in the causative organism, Streptococcus pneumoniae has been compromised due to non-synonymous single nucleotide polymorphisms (nsSNPs) in different penicillin-binding protein (PBP) targets. Carbapenem-resistant S. pneumoniae strains have further constricted the pharmacologically safe therapeutic options. Methods: In-house sequenced whole genomes of meropenem and cefotaxime resistant Indian and global isolates were used to retrieve parent and mutant proteins. Anti-bacterial phtytochemicals (ABPs) from Indian curry-leaf tree Murraya koenigii were identified using database-mining. ABPs were screeened based on pharmacokinetics, and toxicity profiles. Site-specific molecular docking studies revealed ABPs' affinity towards the targets as compared to control drug meropenem. Coarse-grained and normal-mode molecular dynamics simulation further asserted the interactive stability of the chosen compounds. Results: From the whole genomes (n = 28) of meropenem and cefotaxime resistant (MIC ≥0.5 μg/ml) Indian and global isolates, ∼50 nsSNPs in the active-site regions of PBP1A, PBP2B and PBP2X were identified. Based on pharmacological safety and high drug-likeliness, 10 ABPs were funnelled down from 226 ABPs in M. koenigii. A pyrano-carbazole alkaloid koenine was further prioritized as the most efficient candidate based on consistently high binding affinity (binding energies −7.7 to −8.9 kcal/mol), low inhibition constant (0.69-3.5 μM) and low structural fluctuations (<1.1 Å), against mutant targets as compared to meropenem. Conclusion: The study encourages experimental validation of koenine against pneumococci and also promotes the use of similar phytochemical resources for evaluation against emerging drug-resistant pathogens harbouring mutant targets.